(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the integration of multimedia software tools in teaching English to primary school children aged 6-7 years. It examines the psychological and pedagogical principles underlying the use of multimedia in language learning, focusing on the specific developmental characteristics of young learners. The article highlights how multimedia tools—such as interactive videos, games, and audio-visual aids—can enhance foreign language acquisition by engaging multiple senses and catering to the cognitive, emotional, and social needs of children at this critical stage of language development. The article also discusses didactic principles and effective methodologies for integrating multimedia tools into foreign language teaching, offering strategies for organizing exercises that promote vocabulary acquisition, pronunciation, and listening comprehension. Through experimental research, the study further validates the effectiveness of multimedia tools in fostering language skills in first-grade students, demonstrating improvements in their linguistic abilities compared to traditional teaching methods. This research underscores the significance of multimedia integration in early foreign language education, providing practical insights for educators and policymakers aiming to enhance language learning outcomes in primary school education.